2017
DOI: 10.1186/s12884-017-1221-z
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women’s preferences for and concerns about preterm birth prevention: a cross-sectional survey

Abstract: BackgroundAlthough there is a call for patient-centred prenatal care, women’s preferences for and concerns about preterm birth (PTB) prevention have not been well-studied. Therefore, we conducted a cross-sectional survey to determine women’s preferences for PTB prevention and their likelihood of following their healthcare provider’s recommendations for PTB prevention, as well as factors associated with these responses.MethodsA piloted self-administered questionnaire was completed by pregnant women who could re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“… 43 For acceptability, the time to complete the questionnaires ranged from 10 to 30 minutes, with nine studies (45%) reporting such data. 35 , 36 , 38 , 40 , 42 , 43 , 47 , 48 Furthermore, response rates of the questionnaires exceeded 50% as reported by 10 studies. 31 , 33 35 , 38 , 40 , 42 44 , 46 In addition, only two studies showed the highest questionnaire content quality following psychometric analysis; 35 , 44 four studies did not follow the psychometric methods to use the questionnaire measuring patient’s preferences and values since neither did they describe item generation and pilot testing nor did they report the related information of validity, reliability, and acceptability.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“… 43 For acceptability, the time to complete the questionnaires ranged from 10 to 30 minutes, with nine studies (45%) reporting such data. 35 , 36 , 38 , 40 , 42 , 43 , 47 , 48 Furthermore, response rates of the questionnaires exceeded 50% as reported by 10 studies. 31 , 33 35 , 38 , 40 , 42 44 , 46 In addition, only two studies showed the highest questionnaire content quality following psychometric analysis; 35 , 44 four studies did not follow the psychometric methods to use the questionnaire measuring patient’s preferences and values since neither did they describe item generation and pilot testing nor did they report the related information of validity, reliability, and acceptability.…”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, nine (45%) studies did not report the study design, 30 , 34 , 38 , 40 , 41 , 43 , 44 , 46 12 (60%) studies provided training to the study participants, 32 38 , 40 , 41 , 45 , 47 , 49 while four (20%) studies did not report information about patient training. 42 44 , 48 In addition, only five (25%) studies provided the method used to calculate the sample size 35 39 , 39 42 , 42 – 47 and only six (30%) studies investigated patient’s family members. 31 , 34 37 , 49 Finally, 17 (85%) studies provided information assessing patient knowledge and beliefs.30,32–35,37–45,47–49…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations